Analisis Kepatuhan Pajak Pelaku UMKM Pasca Penerbitan Peraturan Pemerintah Nomor 23 Tahun 2018 - Sri Rahayu Rahmadhani; Charoline Cheisviyanny; Erly Mulyani (Universitas Negeri Padang, 2020)
This study aims to analyze the tax compliance of MSMEs after the issuance of Government Regulation No. 23 of 2018. This research is a qualitative research using a phenomenological approach. The Informants were determined using the purposive sampling method. Data was collected by interview and triangulation techniques. Data analysis used was the model of Miles and Huberman is data reduction, data display and conclusions. The results showed that the compliance of MSMEs in Padang City was still low. This is caused by the lack of tax knowledge. It suggests tax officer enhance socialization ad to educate taxpayer.